1991
DOI: 10.1104/pp.96.3.887
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Synthase Expression during Cold Acclimation in Wheat

Abstract: When wheat (Triticum aestivum) seedlings are exposed to a cold temperature (2-40C) above 00C, sucrose accumulates and sucrose synthase activity increases. The effect of a cold period on the level of sucrose synthase (SS) was investigated. Using antibodies against wheat germ SS, Western blots studies showed that the amount of the SS peptide increased during 14 days in the cold, when plants were moved from 230C to 40C. The level of SS diminished when plants were moved back to 230C. Northern blots of poly(A)+ RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 26 publications
8
36
1
1
Order By: Relevance
“…It has been suggested that there is a requirement for the up-regulation of genes involved with sugar metabolism during cold acclimation (Guy, 1990). Evidence for this was demonstrated in winter wheat, where Suc synthase polypeptide and poly(A)+ RNA levels increased with lowtemperature treatment (Crespi et al, 1991). Results of this study also suggest that a phosphoglucomutase gene, encoding an enzyme of the glycolysis/gluconeogenesis pathway, has a higher leve1 of expression during ABA-induced hardening.…”
Section: Discussionsupporting
confidence: 66%
“…It has been suggested that there is a requirement for the up-regulation of genes involved with sugar metabolism during cold acclimation (Guy, 1990). Evidence for this was demonstrated in winter wheat, where Suc synthase polypeptide and poly(A)+ RNA levels increased with lowtemperature treatment (Crespi et al, 1991). Results of this study also suggest that a phosphoglucomutase gene, encoding an enzyme of the glycolysis/gluconeogenesis pathway, has a higher leve1 of expression during ABA-induced hardening.…”
Section: Discussionsupporting
confidence: 66%
“…More recently it was shown that another maize anaerobic protein, Suc synthase, is also inducible by low-temperature conditions (Crespi et al, 1991). Although it is not known whether a11 maize anaerobically inducible genes are also induced by cold stress, the question arises whether regulation of gene expression by both environmental stresses (anaerobiosis and cold) are mediated through the same signal-transduction pathway .…”
Section: Dlscusslonmentioning
confidence: 99%
“…15) In contrast, regulation of the enzymes involved in sucrose synthesis is more complicated under cold stress, 16) often giving conflicting results when various studies are compared. 17,18) We are also interested in the transport of fixed carbon from photosynthesis and the level of glycolysis in cells. The expression levels of two key enzymes, triose phosphate translocator (TPT) and pyruvate kinase (PK; EC 2.7.1.40) have been determined.…”
Section: Detection Of Sugar Accumulation and Expression Levels Of Cormentioning
confidence: 99%